PERBANDINGAN HASIL BELAJAR KORESPONDENSI SISWA YANG DIBERI EVALUASI BENTUK PILIHAN GANDA DENGAN ESSAY TES PADA KELAS X ADMINISTRASI PERKANTORAN DI SMK ERIA MEDAN T.A 2021/2022 - Lastri Lastri; Rijal Rijal (Sekolah Tinggi Pariwisata Mataram, 2022)
This study aims to determine the Comparison of Correspondence Learning Outcomes of Students who were given Multiple Choice Evaluation with Essay Tests in Class X Office Administration at SMK Eria Medan T.A 2021/2022. This research is experimental, namely research that is intended to determine whether or not there is a result of something caused by the subject, namely students. The population in this study were all students of class X OTKP 1 and OTKP 2 totaling 37 students at SMK Eria Medan. The research sample that will be used in this study is class X OTKP1 and OTKP 2 totaling 37 students. The sampling technique in this study is a purposive sample or a purposive sample. The purpose of the sample is to take the subject, not based on strata, random, or area but based on a specific purpose. In this study, the sample came from class X OTKP-1 which consisted of 17 students and class X OTKP-2 which consisted of 20 students. The analytical technique used is a conformity test using a hypothesis test (t test) to test the comparison of student correspondence learning outcomes who are given a multiple-choice evaluation with an essay test in class X OTKP at SMK Eria Medan T.A 2021/2022. Based on the results of the research that has been done, it can be concluded that there is a significant difference in student learning outcomes in correspondence subjects using multiple choice and essay tests of 5,389 then these results are compared with ttable at a significant level of 5%, namely 1,666. Then tcount > ttable (5,389 > 1,666). From the results of the comparison, it can also be concluded that there are differences in student learning outcomes in correspondence subjects using multiple choice and class X essay tests at SMK Eria Medan.